2014
DOI: 10.3389/fnbeh.2014.00140
|View full text |Cite
|
Sign up to set email alerts
|

A novel automated behavioral test battery assessing cognitive rigidity in two genetic mouse models of autism

Abstract: Repetitive behaviors are a key feature of many pervasive developmental disorders, such as autism. As a heterogeneous group of symptoms, repetitive behaviors are conceptualized into two main subgroups: sensory/motor (lower-order) and cognitive rigidity (higher-order). Although lower-order repetitive behaviors are measured in mouse models in several paradigms, so far there have been no high-throughput tests directly measuring cognitive rigidity. We describe a novel approach for monitoring repetitive behaviors du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 36 publications
3
38
2
Order By: Relevance
“…Previous studies also showed that measures of learning can be collected in standardized automated home-cage environments without human interference (Galsworthy et al 2005;Mechan et al 2009;Gallistel et al 2010;Endo et al 2011;Balci et al 2013;Puścian et al 2014;Remmelink et al 2015); however, all these tasks restricted reinforcement schedules to specific times of the day. We here demonstrate that continuous testing is compatible with operant testing which allowed for the short duration of the reversal learning protocol as well as animal paced task participation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed that measures of learning can be collected in standardized automated home-cage environments without human interference (Galsworthy et al 2005;Mechan et al 2009;Gallistel et al 2010;Endo et al 2011;Balci et al 2013;Puścian et al 2014;Remmelink et al 2015); however, all these tasks restricted reinforcement schedules to specific times of the day. We here demonstrate that continuous testing is compatible with operant testing which allowed for the short duration of the reversal learning protocol as well as animal paced task participation.…”
Section: Discussionmentioning
confidence: 99%
“…The number of publications where IntelliCage has been applied as a tool for behavioral testing is growing, although we have not found references directly addressing the role of NTFs in behavior. However, the method has been valuable for investigating the links between neurogenesis and behavior (Vannoni et al, 2014), in characterization of mouse models for Huntington’s disease (Knapska et al, 2013; Knapska et al, 2006; Kobayashi et al, 2013), Alzheimer’s disease (Codita et al, 2010; Ryan et al, 2013; Weyer et al, 2011), Down syndrome (Faizi et al, 2011), autism (Puscian et al, 2014). In addition, IntelliCage has been used as either enriched or stressful environment and combined with measurement of changes in the levels of BDNF and glucocorticoids (Alboni et al, 2015; Branchi et al, 2013; Kulesskaya et al, 2014) provides an excellent ethological surrounding for modeling stress and depression-like behavior in mice.…”
Section: Future Perspectives For the Studies Exploring Neurobiology Omentioning
confidence: 99%
“…More recently, IntelliCage place discrimination tasks have been used to investigate higher-order cognitive functions in both normal and disease model mice. Acquisition and reversal of place discrimination was found to differ between various commonly used inbred mouse strains (Krackow et al 2010;Endo et al 2011), and valproatetreated C57BL/6 mice, used as a model of autism, displayed impairments in place learning associated with perseverative responding (Puscian et al 2014). However, little is known about the neural circuitry that mediates performance on this task.…”
mentioning
confidence: 99%